PENGARUH KEBIJAKAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KEPUASAN KERJA PEGAWAI PADA KEMENTERIAN AGAMA KABUPATEN PINRANG - ., Kasmawati; ., Asmawati (Jurnal Pendidikan Kreatif, 2021)
The objectives of this study are (1) to obtain an overview of human resource development policies in the Ministry of Religion of Pinrang Regency (2) To obtain an overview of employee job satisfaction at the Ministry of Religion of Pinrang Regency (3) To determine whether there is an influence of human resource development policies on employee job satisfaction at the Ministry of Religion of Pinrang Regency. This study uses an expost facto research method which is part of a quantitative research method approach. The population in this study were all employees of the Ministry of Religion of Pinrang Regency, totaling 50 people, so the researchers took all the population as samples using saturated sampling. Saturated sampling is a sampling technique when all members of the population are sampled. The data analysis techniques used in this research are descriptive statistical analysis techniques and inferential statistical analysis techniques using simple linear regression.The results of this study can be concluded: (1) Human resource development policies at the Ministry of Religion of Pinrang Regency are classified as moderate, namely 68% with 34 respondents. (2) Employee job satisfaction at the Office of the Ministry of Religion of Pinrang Regency is classified as moderate at 66% and at this interval as many as 33 respondents. (3) There is an influence between human resource development policies on employee job satisfaction at the Office of the Ministry of Religion of Pinrang Regency seen from the results of inferential statistical analysis obtained, namely > , where is 0.90 and is 0.284 at a significant level of 5% which means Ha is accepted, so that the human resource development policy on employee job satisfaction at the Ministry of Religion of Pinrang Regency.In connection with the results of the research that has been carried out, the implications of the research are as follows: (1) the human resource development policy at the Ministry of Religion is expected to be better in the future than before. 2) job satisfaction of employees carrying out their duties and responsibilities and employees are expected to further improve their skills and performance in carrying out their duties and responsibilities for the advancement of the institution's organization. (3) for further research, it is recommended to conduct research with other material coverage based on human resource development.